A review of the freshwater crabs of Turkey (Brachyura, Potamidae) - Harllo?lu, Muzaffer Mustafa; Farhadi, Ardavan; Harllo?lu, Ayşe Gül (My University, 2018)
The present status of freshwater crabs (Decapoda, Brachyura) in Turkey is reviewed in this study, with the purpose of identifying the exact number of species, their conservation status, and their distribution. In previous records, it was reported that Turkey has nine freshwater crab species belonging to the genus Potamon: Potamon bileki Pretzmann, 1971, P. ibericum (Bieberstein, 1809), P. hueceste Pretzmann, 1962, P. persicum Pretzmann, 1962, P. magnum Pretzmann, 1962, P. potamios (Olivier, 1804), P. setiger Rathbun, 1904, P. rhodium Parisi, 1913, and P. mesopotamicum Brandis, Storch & Türkay, 1998. However, there was no detailed information on species distribution in Turkey. This review is intended to update the distribution of species in the country, and it revealed that populations of three more freshwater crab species (P. karpathos, P. fluviatile and P. hippocrate) also occur; thus, there are currently 12 freshwater crab species in Turkey. In addition, this review provides a distribution map and identifies possible threats to each species. This review can serve decision makers in the development of management strategies to better protect the environments of these species that are facing growing anthropogenic impacts. © 2018 Muzaffer Mustafa Harllo?lu, et al., published by Sciendo.
Keywords: Decapoda; distribution; diversity; threat